Dorsal root ganglion macrophages contribute to both the initiation and persistence of neuropathic pain - Xiaobing Yu (Nature Communications, 2020)
Interactions among spinal dorsal horn neurons and microglia contribute to the induction and maintenance of neuropathic pain after peripheral nerve injury. The authors show that depletion of macrophages in the dorsal root ganglia prevents and reverses ongoing nerve injury-induced hypersensitivity.